Hambatan Psikologi Digital Dalam Pendidikan di Sekolah Dasar - Thohiroh, Nazila Syifa (MAN Insan Cendekia Jambi, 2024)
The development of technology and advancements in education have driven educational institutions to adopt various digital technology tools and applications to improve the effectiveness and efficiency of learning. The COVID-19 pandemic can be considered as the main trigger for the large-scale use of digital technology in the education sector. The current world of education is largely dependent on the use of digital technology, which has brought many benefits, but at the same time, psychological barriers to digital technology have emerged that need to be addressed. These barriers include limited access, attention deficits, stress, lack of social interaction, and the risk of abuse and online crime. It is important for relevant parties to overcome these barriers so that the use of digital technology in education can have a positive impact on students. This paper is written using the Literature Review method, which is conducted for various purposes, including identifying, reviewing, evaluating, and interpreting all available research in an interesting topic area, with a particular relevant research question.